(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article discusses topical issues of methods of teaching Russian as a foreign language (RFL) in modern conditions. The need for transition from the traditional grammatical-translation method to communicative, activity and interactive approaches is emphasized. Modern pedagogical technologies, digital tools and features of the formation of intercultural competence in foreign students are analyzed. The article presents the results of the pedagogical experiment, proving the effectiveness of the proposed integrative approach.